Pengaruh Rendaman Ekstrak Bawang Merah dan Rootone –F Terhadap Pertumbuhan Stek Batang Sungkai (Albertisia papuana Becc.) - Julia R. M. Monis; Yos A. Tangkasiang; Arief R. Hakim; Asro’ L. Indrayanti; Yulia Yustha (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Efforts to cultivate sungkai plants are hampered due to the limitations of good seedlings. Sungkai plants reproduce by seeds and stems (cuttings). This research will try to investigate the effect of using Growth Regulatory Substances (ZPT)against stem cuttings of sungkai plants. The study was designed in the Draft Randomized Complete (CRD) with 2 factors, each with 5 treatments. The factors tested were (1) synthetic auxin (Rootone F) with 5 concentrations, i.e. 20 grams / l (R1), 40 grams / l (R2), 60 grams / l (R3), 80 grams / l (R4) and 100 gram / l (R5); (2) natural auxin (onion extract with 5 concentrations, i.e. 20% (B1), 40% (B2), 60% (B3), 80% (B4) and 100% (B5). Besides that control plots were also carried out, which were not treated at all. Each treatment was repeated 3 times, so in a manner in total there were 33 experimental units (including 3 treatment experimental units control). The results showed that giving Rootone F solution affected the growth of sungkai stem cuttings (Albertisia papuana Becc.) on the observed variabels, namely shoot height, number of leaves, root length, and root wet weight. Giving Rootone F solution to sungkai stem cuttings at a concentration of 80 grams and immersion for 24 hours gave the best effect.